(untitled) (Iranian Journal of Kidney Diseases, 2010)
Introduction. Hyperhomocysteinemia is common in patients with chronic kidney disease. There is a direct relationship between cardiovascular mortality and increase of blood homocysteine. Folic acid is used as common treatment in such patients. Folinic acid, a shortened form of folic acid, is not affected by inhibitors of dihydrofolate reductase enzyme such as methoterxate. This study was performed to evaluate the effect of oral folinic acid on the blood homocysteine level of hemodialysis patients, in comparison with folic acid. Materials and Methods. This clinical trial was performed on 60 hemodialysis patients. The participants were divided into 2 groups to receive either 15 mg of oral folic acid or 15 mg of oral folinic acid, daily. Blood homocysteine levels were measured before dialysis and after the study period. Results. Folic acid and folinic acid decreased the blood homocysteine levels by 33.0% and 28.7%, respectively (P < .001). However, only 3 patients (6.5%) enjoyed a normalized homocysteine level. Conclusions. Our study showed that both folic and folinic acid decreased the blood homocysteine level and no meaningful difference was observed between them; therefore, we suggest they can be used interchangeably.